The hummingbird sign in the clinicoradiological approach to a patient with Parkinson plus: A case report - Velásquez-García, Felipe (2023)
Parkinsonism refers to a heterogeneous clinical syndrome defined by 4 motor symptoms: bradykinesia, rigidity, resting tremor, and postural instability, constituting the classical presentation of Parkinson's disease (PD). However, there are 4 other fundamental etiologies to consider in the differential diagnosis of a predominantly motor neurodegenerative disorder, with important prognostic and therapeutic implications. These are progressive supranuclear palsy (PSP), multiple system atrophy (MSA), corticobasal syndrome (CBS), and dementia with Lewy bodies (DLB), all grouped under the term Parkinson plus syndrome. Here, we present a case of progressive supranuclear palsy whose diagnosis was made by evaluating atypical clinical signs such as rapid progression, predominant axial rigidity, ophthalmoplegia, dysarthria, ataxia, and bulbar disorders, highlighting the crucial role of conventional MRI in assessing mesencephalic atrophy from a mid-sagittal view, a finding known as the hummingbird sign.